PENINGKATAN HASIL BELAJAR PADA PEMBELAJARAN MATEMATIKA MENGGUNAKAN MEDIA MANIPULATIF DI SEKOLAH DASAR - Anes, Albanus; Margiati, K.Y.; Sabri, Tahmid (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Abstract       Problem in this study is Is there an increase in student learning outcomes in mathematicsl learning using manipulative media at Elementary School fourth grade 01 Segonde Bengkayang? " Purpose research  is to describe the improvement of mathematics learning outcomes of fourth grade students of SD Negeri 01 Segonde by using manipulative media ". M etode used is descriptive method with form research action class (PTK ) and is collaborative . The Place research take place in School basic Negeri 01Segonde, class Iv which numbered 14 person with subject class room teacher research and Students class IV. Technique data collector used that is Technique observation Direct and Document observation with tool data collector that is IPKGsheet 1,and IPKG sheet 2and document results Student learning. Research do 2 cycle. Assesment result from design learning (RPP) from cycle I is 3,06 with good category,second cycle 3,59 with categories very good. Asessement results from implementation  learning from cycle I is 3.35 with good category , on the second cycle increased to 3 , 70 category very good . The average assessment of student learning outcomes in the first cycle is 62,43 in the second cycle increased to 69,57. Based on the data obtained could concluded happen enhancerment on every cycle. With so research with use manipulative media to improve student learning out comes in class IV SD Negeri 01 Segonde round will sucsesfull.  Word Key : Learning Outcomes, Manipulative Media, Grade IV Students